O Organizational Culture and Motivation Toward Job Satisfaction of Bank "XYZ" Employees - Asnah, Asnah; Febrianti , Eka; Sabri, Sabri; Antoni, Antoni; Nasfi, Nasfi (International Journal of Social and Management Studies, 2021)
The purpose of this study was to determine work culture and work motivation as well as the joint influence of work culture and work motivation on job satisfaction of XYZ Bank employees in the City of Bukittinggi. For the sake of the image of the bank in the eyes of customers, the name of the bank is called XYZ Bank. This study took data from one of the banking institutions in the City of Bukittinggi, during the research period from February to October 2020, the quantitative research method was using questionnaire data collection techniques. The research variable of organizational culture (X1) and work motivation (X2) as independent variables, while job satisfaction (Y) as the dependent variable, with a population of 50 employees of Bank XYZ, all of them were sampled, using total sampling technique. The results of the research on organizational culture (X1) and work motivation (X2) have a positive and significant effect on job satisfaction of XYZ Bank employees, and simultaneously the variables of organizational culture and work motivation together (simultaneously) have a positive and significant effect on job satisfaction of bank employees XYZ.